A randomized trial to assess the pharmacodynamics and pharmacokinetics of a single dose of an extended-release aspirin formulation. Issue 6 (October 2015) - Patrick, Jeff; Dillaha, Larry; Armas, Danielle; Sessa, William C.
Abstract: Aims. Low-dose acetylsalicylic acid (ASA; aspirin) for secondary prevention reduces cardiovascular disease mortality risk. ASA acetylates cyclooxygenase in the portal circulation and is rapidly (half-life, 20 min) hydrolyzed. Certain patients with cardiovascular disease may exhibit high on-therapy platelet reactivity as a result of high platelet turnover, a process whereby platelets are produced and are active beyond the duration of antiplatelet coverage provided by once-daily immediate-release (IR) ASA. A once-daily, extended-release (ER) ASA formulation using ER microcapsule technology was developed to release ASA over the 24-h dosing interval and reduce maximal plasma concentrations to spare peripheral endogenous endothelial prostacyclin production. Methods. Healthy adults (n = 50) were randomized in a crossover study to receive two different ER-ASA single doses (up to 325 mg) and two different IR-ASA single doses (up to 81 mg) in four periods, each separated by ≥14 days. Pharmacodynamics was assessed by measuring serum thromboxane B2 (TXB2 ), urine 11-dehydro-TXB2, and arachidonic acid-induced platelet aggregation. Pharmacokinetics was determined for ASA and salicylic acid (SA). Results: Both formulations produced dose-dependent inhibition on all pharmacodynamic parameters. Marked inhibition of TXB2 and 11-dehydro-TXB2 was maintained over the 24-h dosing interval after a dose of ≥81 mg ER-ASA or ≥40 mg IR-ASA. The dose required to achieve 50% of maximum TXB2 inhibition with ER-ASA was 49.9 mg versus 29.6 mg for IR-ASA, for a similar maximum pharmacodynamic effect (98.9% TXB2 inhibition). This suggests that an approximately twofold greater ER-ASA dose (162.5 mg) is necessary to obtain the same response as that of IR-ASA 81 mg. Peak ASA concentrations were lower and Tmax was longer with ER-ASA versus IR-ASA. Administration of IR-ASA resulted in a dose-normalized mean Cmax of ASA that was approximately sixfold higher than that for ER-ASA and a Cmax of SA approximately two- to threefold higher than that for ER-ASA. Conclusion. Both ASA formulations showed dose-dependent antiplatelet activity. Compared with the IR-ASA, ER-ASA released active drug more slowly, resulting in prolonged absorption and lower systemic drug concentrations, which is expected for an ER (24-h) formulation.